Subtypes in PTSD for Veterans: Do Similar Profiles Exist in Polytrauma Patients? - Palmer, Glen A.; Palmer, Daniel G. (Journal of Loss & Trauma, 2021)
Previous research has suggested the presence of various subtypes in posttraumatic stress disorder (PTSD) in patient populations. The purpose of this study was to explore the presence of various subtypes in PTSD in veterans referred for traumatic brain injury evaluation. As a focus of this analysis, comorbid symptoms (i.e., anxiety, depression, and neurobehavioral) were used to divide a polytrauma sample of veterans with diagnosed PTSD into clusters. The presence of a three-cluster solution was identified and validated with two types of cluster analysis. Discussion of the nature of the three subtypes of PTSD and implications for treatment are presented.